PENGGUNAAN PEMANIS RENDAH KALORI STEVIA PADA VELVA TOMAT (Lycopersicum esculentum mill) - Astuti, Zenita Mulya; Ishartani, Dwi; Muhammad, Dimas Rahadian Aji (Jurnal Teknologi Hasil Pertanian, 2021)
The purpose of this research was to determine the effect of velva tomato formula with different proportions of sugar and stevia on the physical, chemical, and sensory of tomato velva. The best tomato velva with sweetener stevia was then determined based on the physical, chemical and sensory characteristics. This research used a completely randomized design (RAL) of one factor which was the propotions of sweetener stevia (K: 50 g sucrose; F1: 39.5 g sucrose and 0.75 g stevia; F2: 29 g sucrose and 1.5g stevia; F3: 19.5 g sucrose and 2.25 g stevia; and F4: 8 g sucrose and 3 g stevia). The result show tat propotions of stevia significantly affects physical characteristics (total dissolved solids, melting power, and overrun), chemical (total calories), and sensory (taste, texture, and overall). While the formula modification has no significant effect on vitamin C and lycopene content. The more proportion of stevia and the less proportion of sucrose reduced total calories, melting power, and total dissolved solids and at the same time increased overrun. The most preferred formula was F1 (39,5g sugar and 0,75g stevia sweetener) which has an overrun of 28.09%, total dissolved solids of 8.43 oBrix, melting power of 13.09 minutes and total calories of 328.65 cal/g.